If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 7 = 11 + -2n Reorder the terms: 7 + 2n = 11 + -2n Solving 7 + 2n = 11 + -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. 7 + 2n + 2n = 11 + -2n + 2n Combine like terms: 2n + 2n = 4n 7 + 4n = 11 + -2n + 2n Combine like terms: -2n + 2n = 0 7 + 4n = 11 + 0 7 + 4n = 11 Add '-7' to each side of the equation. 7 + -7 + 4n = 11 + -7 Combine like terms: 7 + -7 = 0 0 + 4n = 11 + -7 4n = 11 + -7 Combine like terms: 11 + -7 = 4 4n = 4 Divide each side by '4'. n = 1 Simplifying n = 1
| b^2+4b-12/2b^2-18 | | 8=3y+5y-24+16 | | 20=4m/9 | | -1/2x=14 | | 3x+13=-x-15 | | 5x-15=7x+25 | | -5=4x-21 | | -4(5y-5)-y=-4(y-5) | | 73=59(108+f) | | 90x^2-120+40=0 | | 1.12+1.25a=8.62 | | x^2+17x+36=0 | | -x(2+4)+40=28 | | a-10=-5a+2 | | -53=-7x+3 | | -8+4x=8 | | -53=-7x | | -4x-2+6=9 | | -2x+4ifx=7 | | 50m+2y=7y | | -4x+-2+6=9 | | 4x+-2x+6=9 | | 2x+4=5x+9 | | -9(x-1)=-36 | | 8=1-2n+5 | | 5/3w-7/4=-w-4/3 | | -6-3x=27 | | -45=9(-2+x) | | -4x+18=-6 | | -x+x-4=2 | | -3p=-27 | | 5a^2=25a |